Investigating the Facilitating Factors of Drug Use Based on Personality and Ethnic Characteristics of Guilan Province - Borjali, Ahmad; Eskandari, Hosein; Sohrabi Asmroud, Faramarz; Mohajer, Yahya; namazi, Davood (Novelty in Biomedicine, 2021)
Abstract Background: Identifying ethnic and personality facilitation factors in drug use help to better diagnose and treat addiction identifying facilitation factors. It provides timely counseling, and psychological services can be partially preventable for addicts. This study aimed to investigate factors facilitating drug use based on ethnic and personality characteristics of Guilan province using the Cloninger personality system. Materials and Methods: The study population consisted of four subcultures of Guilak, Talesh (Turk), Kord and others called Fars. The sampling method in this study was a mixed-method; the sample size was at least 200 people. The present study used data in the field section of Cloninger's personality and character questionnaire to determine personality components and their relationship. They were used with current norms. This study used in-depth interviews, observation and review of documents (questionnaires) and conventional oral literature on drug use. Results: This study showed that between ethnic facilitation factors (drug and drug counseling, folk beliefs in oral literature, and beliefs about rituals and companionship) and personality traits (nature and character), except the avoidance factor at the significant level of 0.01, there was a significant and positive relationship. Variables of personality traits/"nature and character" and components of perseverance, novelty, reward-dependence, self-direction, cooperation can predict common beliefs in the propensity to medication and therapy. The personality facilitator variable of "nature and character" and all its components, except for themselves, was able to predict the popular beliefs existing in oral literature. The personality facilitator variable of "nature and character" and the components of novelty, reward-dependence, and cooperation could predict common beliefs about rituals and companionship. Conclusion: Research showed a significant relationship between ethnicity and propensity for drug and drug counseling, popular beliefs in oral literature, and celebration and celebration beliefs.